Analyzing the Gacha System in Genshin Impact: odds, mechanics, and player enticement - Sagguneswaraan Thavamuni; Mohd Nor Akmal Khalid; Kohda, Youji; Iida, Hiroyuki (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research paper delves into analyzing the Gacha system in the popular video game Genshin Impact, focusing on understanding the odds, mechanics, and player engagement associated with this unique gaming feature. Gacha games, including Genshin Impact, are designed to captivate and retain players by offering a randomized reward system with the potential for obtaining rare and desirable items. This study aims to shed light on the underlying factors that make the Gacha system attractive to players and explore its psychological impact on player engagement. By conducting a small-scale experiment, we plan to monitor the heart rate of respondents to study the emotional impacts of playing the Gacha. The number of attempts made during the experiment will then be analyzed using motion in mind theory to further explore the impact on the player’s minds. The findings of this research can contribute to responsible gaming practices and inform game developers in creating engaging and enjoyable experiences for players within the realm of Gacha games.